Recent Advances on Lignocellulosic-Based Nanopesticides for Agricultural Applications - Lima, Pedro Henrique Correia de [UNESP]; Antunes, Débora Ribeiro [UNESP]; Forini, Mariana Monteiro de Lima [UNESP]; Pontes, Montcharles da Silva; Mattos, Bruno Dufau; Grillo, Renato [UNESP] (Frontiers, 2021)
Controlled release systems of agrochemicals have been developed in recent years. However, the design of intelligent nanocarriers that can be manufactured with renewable and low-cost materials is still a challenge for agricultural applications. Lignocellulosic building blocks (cellulose, lignin, and hemicellulose) are ideal candidates to manufacture ecofriendly nanocarriers given their low-cost, abundancy and sustainability. Complexity and heterogeneity of biopolymers have posed challenges in the development of nanocarriers; however, the current engineering toolbox for biopolymer modification has increased remarkably, which enables better control over their properties and tuned interactions with cargoes and plant tissues. In this mini-review, we explore recent advances on lignocellulosic-based nanocarriers for the controlled release of agrochemicals. We also offer a critical discussion regarding the future challenges of potential bio-based nanocarrier for sustainable agricultural development.
Keywords: biopolymers; circular bioeconomy; lignocellulosic materials; nano-enabled agriculture; nanopesticides; nanotechnology; sustainable agriculture